APPLICATION OF MULTI-ITEMS EPQ MODELS IN COURSE MATERIALS MANAGEMENT: TOWARDS BUILDING A DECISION SUPPORT SYSTEM FOR THE NATIONAL OPEN UNIVERSITY OF NIGERIA - Adoga, Peter Ikpe; Muazu, H. G.; Barma , M. (FUDMA JOURNAL OF SCIENCES, 2022)
The classic multi-item Economic Production Quantity (EPQ) model was applied in this research to solve the Course Materials production problem of National Open University of Nigeria (NOUN). The EPQ model is one of the essential components of the proposed Decision Support System (DSS) for production and inventory management of course materials in NOUN. Python programming was used to develop the DSS to give a flexible interface that is easy to use by all users. The EPQ module of the DSS generated essential outputs which answers basic questions such as when to produce, how much of each item to produce per production run, the cost of producing each item and the interval between the productions run. Testing of the EPQ module was carried out using test data. When implemented, the proposed solution will enhance decision making in the area of Course Material production at NOUN printing press and reduce the difficulties encountered by staff when using manual processes to resolve complex models on regular basis
Keywords: Course Materials Production, Multi-Item Economic Production Models, EPQ, Multi-item Production Cycle, Python Programming.